Humanitarian vs. development aid for refugees: evidence from a regression discontinuity design - MacPherson, C; Sterck, O (Centre for the Study of African Economies, 2019)
Assistance to refugees living in camps is shifting from a humanitarian model, based on care and maintenance, to a development model that promotes refugee self-reliance through income generating activities, market development, and cash transfers. Evidence on the effects of this paradigm shift is limited. Exploiting a regression discontinuity design, this paper tests whether the adoption of a development approach to refugee assistance in a new settlement in Kenya has a positive impact in the short run. We find that refugees benefiting from the new approach have better diets and perceive themselves as happier and more independent from humanitarian aid. We find no effect on assets and employment. These effects appear to be driven by the switch from food rations to cash transfers and by the wider promotion of kitchen gardens. Our findings argue in favor of the development approach to refugee assistance, which is cheaper and leads to better outcomes.